2017
DOI: 10.1063/1.4986346
|View full text |Cite
|
Sign up to set email alerts
|

The effect of finite pore length on ion structure and charging

Abstract: Nanoporous supercapacitors play an important role in modern energy storage systems, and their modeling is essential to predict and optimize the charging behaviour. Two classes of models have been developed that consist of finite and infinitely long pores. Here, we show that although both types of models predict qualitatively consistent results, there are important differences emerging due to the finite pore length. In particular, we find that the ion density inside a finite pore is not constant, but increases … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 61 publications
1
55
0
Order By: Relevance
“…[6]. Similarly, in a combined MC and MD study, Breitsprecher et al [54] also observed that the counter-ion adsorption was preceded by co-ion desorption, although they did not report on any phase transition.…”
Section: A Positive Transfer Energiesmentioning
confidence: 93%
“…[6]. Similarly, in a combined MC and MD study, Breitsprecher et al [54] also observed that the counter-ion adsorption was preceded by co-ion desorption, although they did not report on any phase transition.…”
Section: A Positive Transfer Energiesmentioning
confidence: 93%
“…Moving to ILs confined in slit-like pores, several groups 38,39 used simulations to predict oscillations of the capacitance as a function of the pore size. Further work insisted on the importance of pore length 40 and on the necessity to account for the pore size distribution to interpret the experimental data 41 .…”
Section: Introductionmentioning
confidence: 99%
“…Considering all of the known mechanisms at the same time is not possible, especially in experimental [15][16][17][18] and analytical 11 studies. Because of that, there are different methods invented and used for EDLS simulations such as Molecular dynamics (MD) [19][20][21][22] , Monte-Carlo 23,24 , lattice model 7 , density functional theory (DFT) 13,25 , mixed DFT with MD and post-HartreeFock calculation 6 , and machine-learning [26][27][28] . In addition, modeling and simplifications in simulations gives us some hints about the ongoing microscopic processes in EDLC.…”
mentioning
confidence: 99%
“…The geometry of the electrodes is an important factor of supercapacitors that highly affects its performance 22 . There are numerous researches on the different electrodes geometries such as, planar electrodes 20,21 , slit-pores 17,23,29 , combining flat and porous electrodes 30 , cylindrical pores 29,31 , spherical electrodes 31 , carbon nanotubes forest 32 , mathematically flat electrodes vs atomic structured electrodes 33 , atomic rough vs atomic non-rough electrode surfaces 10 and so on.…”
mentioning
confidence: 99%
See 1 more Smart Citation